Analysis of Green Practices Implementation at FourStar by Trans Hotel Restaurant - Gede Ari Ambara Putra; Ni Ketut Bagiastuti; Ni Nyoman Sri Astuti; I Ketut Suparta; I Ketut Suja (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This study aims to determine the implementation of green practices that have been implemented and which need to be improved at the FourStar by Trans Hotel restaurant. Green Practice is an action to protect the environment and the resulting product is less damaging to the environment. Restaurants that imple-ment green practice usually focus on reduce, reuse, and recycle as well as energy and efficiency. Research methods: The research data were sourced from participatory interview and observation methods at the research location which were then processed us-ing triangulation techniques. Findings: The results of the study show that the implementation of green practic-es has been implemented properly and adequately in restaurants although there are several indicators of green practice that still need to be improved. Implication: Indicators that need to be maintained include the use of recyclable containers, the use of energy-efficient lighting and the use of a temperature com-fort control system, as well as the installation of signs and policies that need to be implemented, and indicators that need to be improved are educating the pub-lics about green practices in a sustainable manner, Implementing funding for ac-tivities that support environmentally friendly direction and donating organic wastes as the use of animal feed for the community.